Hardcore smoking among daily smokers in male and female adults in 27 countries: a secondary data analysis of Global Adult Tobacco Surveys (2008-2014) - Chandrashekhar T Sreeramareddy; Joanne Hon; Anshad Mohamed Abdulla; Sam Harper (Inishmore Laser Scientific Publishing Ltd, 2018)
# Background "Hardcore smokers" (HCS) who do not want to quit make it more difficult for tobacco control efforts to further reduce smoking prevalence. We aimed to quantify the burden of HCS among daily smoking adult males and females in 27 countries. # Methods We used Global Adult Tobacco Survey (GATS) data to estimate the prevalence of HCS ie, daily smokers who smoke within 30 minutes after waking up, smoke ≥10 cigarettes per day, have not made any quit attempts during previous 12 months or have no intention to quit at all during the coming 12 months. For each GATS country, we estimated sex-wise, weighted and age-adjusted prevalence of daily smoking and HCS. # Results Overall weighted population prevalence (%) of HCS was highest in Greece (21.0), followed by Russia (13), Poland (9.4), Romania (9.0), and Ukraine (8.9) and lowest in Nigeria (0.4). Estimated number of HCS (in millions) was highest in China (35.8) followed by India (28.2), Russia (18.5), Indonesia (16.1) and lowest in Panama (0.03). The proportion (%) of daily smokers classified as HCS was highest in Greece (56.2%) followed by Russia (42.2%), Ukraine (37.2) and Poland (36.2) and lowest in Mexico (8.29). Overall, proportion of HCS was higher among males in all countries. However, in Greece, Russia, Romania, Ukraine and Poland both population prevalence of HCS among women and proportion of HCS among daily smoking women was higher than in other countries. # Conclusions At the country-level, a higher daily smoking rates also suggest a higher proportion of HCS. Countries with greater burden of HCS pose greater challenges to tobacco control efforts specifically towards tobacco cessation interventions. Interventions to reduce tobacco use and smoking-related mortality may need to be altered in populations with high proportions of HCS.